Determinants of employees’ awareness for universal newborn hearing screening: evidence from Malaysia - Chew Abdullah, Nor Azimah; Zakaria, Mohd Nizar; Abdul Majid, Abdul Halim; Hamzah, Sulaiman; Ismail, Abdussalaam Iyanda; Mukari, Siti Zamratol Mai S. (International Economic Society, 2017)
This paper focusses on the employee awareness of Universal Newborn Hearing Screening (UNHS) in selected public hospitals in Malaysia in which employees’ awareness’s relationship with factors like human resource practices, program layout, screening instruments and screening techniques were empirically examined. A cross sectional survey was adopted for data collection and Smart PLS 2.0 m3 software was employed to test hypotheses. 63 questionnaires were distributed to the employees who involved in UNHS program, but 51 completed questionnaires, representing 81% response rate, were returned and usable for analysis. The R square value was 0.312 which indicated that exogenous latent variables explain 31% of the variance of the endogenous latent variable which is rather moderate. Findings from PLS structural model revealed insignificant relationship between screening techniques and employee awareness, screening instruments and employee performance, and human resource practices and employee awareness. Conversely, the result showed a significant relationship between program layout and employee awareness. The result indicates significant relationship between program layout and employee awareness while other variables (screening techniques, screening instruments, human resource practices), were found to be insignificantly related to employee awareness. Overall, issues of human resources are critical in ensuring successful UNHS program implementation. Program productivity and patient coordination can be improved by modifying certain elements in the layout design, and factors like test site, clinical conditions of the newborn, and carrying out the test prior to hospital discharge are essential in determining effective UNHS screening.